Benzyl N-{(1S)-2-hydroxy-1-[N'-(2-nitrobenzylidene)hydrazinylcarbonyl]ethyl\ carbamate - de Souza, M.V.N.; Pinheiro, A.C.; Tiekink, E.R.T.; Wardell, S.M.S.V.; Wardell, J.L. (International Union of Crystallography, 2010)
The carbamate and hydrazone groups in the title compound, C(18)H(18)N(4)O(6), are approximately orthogonal [dihedral angle = 83.3 (4)degrees], and the carbonyl groups are effectively anti [O=C...C=O torsion angle = -116.2 (7)degrees]. The conformation about the imine bond [1.295 (11) A] is E. The crystal packing is dominated by O-H...O and N-H...O hydrogen bonding, which leads to two-dimensional arrays in the ab plane.